Arabic Language Learning Based on Group Discussion in Arabic Text Comprehension of Class X Students at MAN I Medan - Marwanda, Tengku Sinar; Zulheddi, Zulheddi (Borneo Journal of Language and Education, 2025)
Arabic holds a central role in the world of Islamic education, especially in madrasas, as it is the primary language for understanding the Qur'an, hadith, and classical Islamic literature. However, in practice, many madrasa students face difficulties in understanding Arabic texts, primarily due to limitations in vocabulary and grammatical structure. One potential method to address this issue is the group discussion method, which allows students to brainstorm ideas, clarify meanings, and build a shared understanding of the text being studied. This study aims to analyze the group discussion-based learning method in improving the understanding of Arabic texts among grade X students at Madrasah Aliyah Negeri 1 Medan. Specifically, this research explores the factors influencing students' understanding of Arabic texts as well as the impact of implementing group discussions in overcoming learning barriers. The research method employed is a descriptive qualitative approach, with data collection techniques including interviews, observations, documentation, and questionnaires. The research subjects consisted of Arabic teachers and grade X students. The results of the study indicate that the application of the group discussion method has a significant impact on improving students' understanding of Arabic texts. Students became more active, motivated, and able to enhance their vocabulary and understanding of Arabic language structure. Prior to the implementation of this method, only about 50% of students understood Arabic texts; however, after its application, this figure increased to 85%. The implications of this study suggest that group discussions are an effective strategy and should be more widely applied in Arabic language learning in madrasas.